FBN2 pathogenic mutation in congenital contractural arachnodactyly with severe skeletal manifestations - Yazhou Huang; Xingxin Fang; Linya Ma; Jibo Zhang; Chao Wang; Taoran Gao; Dan Peng (Molecular Genetics and Metabolism Reports)
Background: Congenital contractural arachnodactyly (CCA) is a rare autosomal dominant connective tissue disorder caused by mutations in the fibrillin-2 (FBN2) gene, characterized by crumpled ears, arachnodactyly, camptodactyly, dolichostenomelia, large-joint contractures and thoracolumbar scoliosis. Variations in the FBN2 gene primarily include missense mutations and splice sites mutations. It is crucial to clarify whether missense mutations in the FBN2 gene affect mRNA splicing. Methods: We identified a novel pathogenic missense variant (c.3472G > C, p.Asp1158His) in exon 26 of the FBN2 gene using whole-exome sequencing (WES) and Sanger sequencing. In vitro, both the wild-type and mutant minigenes were successfully inserted into the pcMINI and pcMINI-C vectors to verify the impact of this variant on FBN2 mRNA splicing. We utilized CLUSTALW to perform multiple sequence alignment to compare the evolutionary conservation of this variant and employed AlphaFold2 to predict the protein structure of the mutant. Results: The likely pathogenic missense mutation (c.3472G > C) results in the amino acid at position 1158 of the FBN2 changing from aspartic acid (Asp) to histidine (His). Furthermore, DNA multiple sequence alignment indicates that this site is highly evolutionarily conserved. Functional assays and structure prediction indicated that the missense variant located at the edge of exon 26 of FBN2 does not affect RNA splicing, instead, it changes the structure and function of the protein by altering the amino acid sequence. Conclusion: This study enriches the pathogenic spectrum of CCA. Our research provides new insights for the diagnosis of CCA and may have an impact on genetic counseling.